Food waste as organic fertilizer - Muhammad Asyraff Zubir, 1995-, author (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2018)
Project Paper (Sarjana Muda Kejuruteraan (Awam)) - Universiti Teknologi Malaysia, 2018